A movimentação do sujeito aluno-professor entre saberes das práticas de ensino de inglês - Passini, Michele Andreza Teixeira (2011)
This study aims at analyzing the movement of the student-teacher subject in knowledge domains, based on the theory of French Discourse Analysis. Since 1998, with the publishing of National Curricular Parameters, changes may be observed regarding teaching practices. Based on that, these student-teachers are in a transitory position, between studying and teaching and they move among divergent knowledge domains in reference to their understanding of the English learning and teaching processes. We intend to observe, by analyzing the linguistic materiality, the discursive processes to perceive how the studentteacher subjects identify themselves with these knowledge domains. In order to do so, we consider the School Discursive Formation which due to its heterogenic aspect allows subject positions related to the traditional English teaching practices as well as the new English teaching practices. Our corpus consists of 28 discursive sequences taken from an archive composed of a research instrument and class memories written by nine student-teachers during their teaching training of their Teaching course in the second semester of 2010 in a university of Rio Grande do sul. In the first chapter, called "The English teaching at school", we observe the legitimation of school teaching and then the evolution of the English teaching practices based on the position taken by the federal government in the enactment of the guideline and bases law, firstly in 1971 and later in 1996. This way, we continue reflecting about the socialization through the school and then we approach the relationship between school and ideology. In the second chapter we present the theoretical aspects in which we based our analysis, focusing on the notion of subject through the years, but also considering other basic concepts of the theory. Along the first two chapters, we present 14 discursive sequences with illustrative purpose. Finally, in the third chapter we consider the methodological procedures as well as the analysis of 14 discursive sequences, which are organized in four sections. In conclusion, we emphasize the heterogeneity of the subject, which is constituted by several sayings and this way they cannot escape from knowledge conflicts